PERENCANAAN STRUKTUR INSTALASI PENGOLAHAN AIR LIMBAH RUMAH PEMOTONGAN HEWAN MENGGUNAKAN METODE ACTIVATED SLUDGE (Studi Kasus Rumah Pemotongan Hewan Pulo Gadung Jakarta Timur) - Putra, Wira Agung Syah; Musalamah, Sittati; Rahmayanti, Henita (LPPM, Universitas Negeri Jakarta, 2020)
This reasearch aims to plan the wastewater treatment unit resulting from the activities of slaughterhouses (RPH) located in RPH Dharma Jaya Pulo Gadung. In planning RPH waste water treatment using Activated Sludge (active sludge) system. This wastewater treatment system will be planned in RPH Dharma Jaya Pulo Gadung neighborhood, East Jakarta. The results of the planning of a container tub, sedimentation tub and aeration tub with a total area of ​​114 m² overall. The 5 x 4 x 3 m container uses a concrete structure with 8 ø 20 and ø 12 - 100 mm reinforcement bars on its walls and 8 ø 20 and ø 12 - 125 mm bars on the bottom plate of the tub. In the first 3 x 1 x 3 m racking basin using a concrete structure with 8 ø 16 and ø 12 - 125 mm reinforcement on its walls and 8 ø 20 and ø 12 - 75 mm bars on the bottom plate of the tub. In the aeration tub with dimensions of 3 x 2 x 2.3 m using a concrete structure with 6 ø 16 and ø 12 - 100 mm reinforcement on the walls and reinforcement 6 ø 20 and ø 12 - 125 mm on the bottom plate of the tub. For the connecting channel with Q max of 2.85 m³ / sec we obtain the width and channel depth b = 14 cm and d = 7 cm for the channel from Bar Screen to the container. For the channel from the reservoir to the settling tub with Q max of 2.37 m³ / sec obtained b = 14 cm and d = 7 cm. And the channel from the settling tub to the aeration bath is 2.04 m³ / sec with the length b = 12 cm and d = 6 cm. Keywords: activated sludge, planning, wastewater treatment